Volatile Organic Compounds From Lysobacter capsici AZ78 as Potential Candidates for Biological Control of Soilborne Plant Pathogens - Vlassi, Anthi; Nesler, Andrea; Perazzolli, Michele; Lazazzara, Valentina; Büschl, Christoph; Parich, Alexandra; Puopolo, Gerardo; Schuhmacher, Rainer (Frontiers in Microbiology, 2020)
The genus Lysobacter includes several bacterial species which show potential for being used in biological control of plant diseases. It was shown recently that several Lysobacter type strains produce volatile organic compounds (VOCs) which controlled the growth of Phytophthora infestans in vitro when the bacteria were grown on a protein rich medium. In the present study, Lysobacter capsici AZ78 (AZ78) has been tested for its potential to produce VOCs that may contribute to the bioactivity against soilborne plant pathogens. To this end, split Petri dish assays of bacterial cultures have been combined with GC-MS measurements with the aim to reveal the identity of the VOCs which inhibit the growth of Sclerotinia minor, Pythium ultimum and Rhizoctonia solani. While AZ78 completely suppressed the growth of S. minor and P. ultimum, the growth of R. solani was still reduced significantly. The GC-MS analysis revealed 22 VOCs to be produced by AZ78, the majority of which were (putatively) identified as mono- and dialkylated methoxypyrazines. Based on additional cultivation and GC-MS experiments, 2,5-dimethylpyrazine, 2-ethyl-3-methoxypyrazine and 2-isopropyl-3-methoxypyrazine were selected as presumable bioactive compounds. Further bioassays employing indirect exposure to standard solutions (1 mg to 10 mg per Petri dish) of the synthetic compounds via the gas phase, revealed that each of these pyrazines was able to suppress the growth of the pathogens under investigation. The results of this study highlight the possible future implementation of pyrazine derivatives in the control of soilborne plant diseases and further support the biocontrol potential of L. capsici AZ78.